Factors associated with congenital malformations among live births in Brazil: SINASC 2017 Data (Brazilian Journal of Health Research, 2023)
Introduction: Congenital malformations are structural or chromosomal problems that significantly affect child development and health. Objectives: To know the prevalence and sociodemographic factors associated with congenital malformations according to the data from the Information System for Life Births (SINASC) of the year 2017. Methods: Cross-sectional study analyzed 2,923,535 live births based on data obtained from SINASC in the year 2017. To assess the outcome, the presence of congenital malformations of newborns at the time of delivery was considered. To test associated factors, sociodemographic variables were considered. Statistical associations were assessed using Poisson regression. Results: The prevalence of congenital malformations was 0.88% (0.87: 0.90) 95% CI. The maternal age, the region of the country, the sex of the newborns and the race / skin color of the mother showed a statistically significant association with the outcome. Conclusion: Knowing the enormous impact that these malformations have, this study is of fundamental importance to help understand and develop measures that enable the prevention of congenital malformations such as, the indispensable role of gynecologists in advising and guiding their patients on the risks of pregnancy in old age, together with policies that fight against gender inequality in the labor market, an interference factor for the choice of maternal age in less secure age groups.
Keywords: Congenital abnormalities; Newborn; Maternal age; Epidemiology